Gender differences in foreign language classroom anxiety: Results of a meta-analysis - Piniel, Katalin; Zólyomi, Anna (Studies in Second Language Learning and Teaching, 2022)
Exploring language learners’ anxiety is not a neglected area of inquiry in applied linguistics research, which can primarily be attributed to the publication of the Foreign Language Classroom Anxiety Scale (FLCAS), an influential instrument developed by Horwitz et al. (1986) to measure language anxiety. An ever-growing array of studies has employed the FLCAS and analyzed the underlying relationship between the focal construct and foreign language achievement, various individual difference variables and a variety of demographic variables, such as learning experiences, age, and gender. Despite the considerable number of publications, studies focusing on biographical variables and language anxiety have not been conclusive. The aim of the present meta-analysis is to analyze 48 studies that employed the FLCAS to look at the potential gender differences with respect to language anxiety. Although there is great variation in the methodological and reporting practices in the studies included, and findings show a tendency for females to experience higher foreign language anxiety, gender-related differences are not statistically significant. The results of moderator analyses showed that neither age nor target language, regional context, or, in the case of university students, their majors, influence this relationship.